Expressing p-stable semantics based on stable semantics - Osorio, Mauricio; Carballido, Jose Luis; Zepeda, Claudia (2010 20th International Conference on Electronics Communications and Computers, 2010)
We study one of the semantics that is useful to formalize NMR, called the p-stable semantics. We explore the relation between the p-stable and the stable semantics. We give a condition under which the two semantics agree in the case of normal programs.